Perancangan Logo Paguyuban Kinanthi Macapat Sidoarjo - Larasati, Anindya Laksmi; Wulandari, Sri; Setiawan, Bayu (IAI Nasional Laa Roiba Bogor, 2026)
The Kinanthi Macapat Sidoarjo Community is a community or group that focuses on the preservation and development of the art of macapat songs, which is a form of traditional Javanese poetry. In addition, this community also strives to reach the wider community to increasingly recognize and appreciate this macapat cultural heritage. With various efforts made, Kinanthi Macapat Sidoarjo is committed to maintaining and developing this very valuable cultural heritage, so that it remains alive and known to future generations, Kinanthi Macapat Sidoarjo really needs help in creating attractive and effective branding media, one of which is creating a logo for the Kinanthi Macapat Sidoarjo Community itself. In this design, a mixed method methodology will be used in collecting data that will be used, which will use qualitative and quantitative methods. In this design, the qualitative method can be applied through interviews, observations and literature studies. While the quantitative method is used through questionnaires. To obtain in-depth information about how teenagers view macapat songs.